The clinical value of serum sST2 and cfDNA in guiding evidence-based nursing care for children with severe pneumonia complicated by myocardial damage - Du, Meng (Journal of Medical Biochemistry, 2025)
Abstract Objective: The study sought to investigate how serum sST2 and cfDNA can be used to inform evidence-based nursing practices for children with severe pneumonia and myocardial damage.Methods:100 children with severe pneumonia complicated with myocardial damage were recruited as research subjects.Following assessment of serum sST2 and cfDNA concentrations, the individuals were categorized into a control cohort (receiving standard treatment, n=50) and an experimental cohort (receiving evidence-based treatment guided by serum sST2 and cfDNA markers, n=50). Collected were the general details of the two patient groups.Biochemical analysis of changes in patient serum sST2 and cfDNA was performed before and after care.Echocardiography was used to measure the left ventricular ejection fraction (LVEF) and left ventricular internal diameter (LVIDd) both before and after treatment of the patient.Levels of procalcitonin and C-reactive protein were assessed using enzyme-linked immunosorbent assay (ELISA) before and after patient treatment, while the white blood cell count in blood samples was determined using an automated hematology analyzer.The patients’ pneumonia resolution and length of hospital stay were compared.Patient satisfaction with care plans was compared through rating questionnaires.Results:The general information of the two groups of patients showed no significant difference (P>0.05).Prior to receiving nursing care, there were no significant variations in serum sST2 and cfDNA levels among the two patient groups (P>0.05).Following the nursing period, the observation group exhibited decreased levels of serum sST2 and cfDNA compared to the control group (P<0.05).Prior to nursing care, there were no significant variations in left ventricular ejection fraction and left ventricular internal diameter in diastole among the two cohorts of patients (P>0.05).Following nursing, the observation group exhibited a higher LVEF compared to the control group, along with asmaller LVIDd (P<0.05).Prior to receiving nursing care, there were no significant variations in procalcitonin, hs-CRP, and white blood cell count between the two patient groups (P>0.05).Following care, the observation group exhibited decreased levels of procalcitonin, hs-CRP, and white blood cell count compared to the control group (P< 0.05).In the observation group, the duration of pneumonia remission and hospitalization was significantly shorter compared to the control group (P<0.05). Conclusion: The importance of serum sST2 and cfDNA indicators in evidence-based nursingfor children with severe pneumonia and myocardial damage is highlighted, showing significant improvement in treatment outcomes and patient satisfaction, confirming the crucial role of these biomarkers in enhancing nursing care plans.